Dzyadyk’s Technique for Ordinary Differential Equations Using Hermitian Interpolating Polynomials - Rizk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For the case of Hermitian interpolation, we consider the approximation-iterative method introduced by Dzyadyk. We construct a practical algorithm.